ANALISIS PENGARUH KUALITAS PELAYANAN, FASILITAS DAN NILAI PELANGGAN TERHADAP KEPUASAN PELANGGAN PADA BENGKEL â€OCEAN AUTO WHEELSâ€ DI SEMARANG - Indianto, Oceano; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2015)
Customer satisfaction is the level of one's feelings after comparing the performance (results) are perceived, compared with expectations. Satisfied customers is known after making a purchase, depending on the offer 's performance in fulfilling the expectations of the buyer. If performance meets expectations, the customer is satisfied. Many factors can affect customer satisfaction, such as service quality, facilities and customer value. Car Repair Ocean Auto Wheels, Jl . Ruko Purianjasmoro Block EE1 / 1 Semarang is a special workshop engaged in car legs. Currently, customers who visit Ocean Auto Repair Wheels tend to go down, because of discomfort when doing car maintenance. From some customer complaints, the vast majority were on workmanship complaints less rapidly (2 complaints), heat, long queues and a less bulky that each 1 complaint per month. Based on complaints show that there is customer unsatisfaction on Car Repair Ocean Auto Wheels. Based on these descriptions, so, the purpose of this study was to analyze the effect of service quality, facilities and customer value on customer satisfactionThe population in this study is that customers do car care at Ocean Auto Wheels Repair, Jl. Ruko Purianjasmoro Block EE1 / 1 Semarang unknown number. The samples in this study were 100 customers. Sampling technique in the study conducted by purposive sampling technique. Data type is primary. Methods of data collection using questionnaires. The analysis technique used is multiple regression.The results of the analysis using SPSS showed that service quality positive and significant effect on customer satisfaction. Facilities positive and significant effect on customer satisfaction. Customer value positive and significant effect on customer satisfaction.